Attraction of the sand fly Nyssomyia neivai (Diptera: Psychodidae) to chemical compounds in a wind tunnel - Machado, Vicente Estevam [UNESP]; Correa, Arlene Goncalves; Goulart, Thais Marchi; Rocha Silva, Flavia Benini da [UNESP]; Samillan Ortiz, Dennys Ghenry; Pinto, Mara Cristina [UNESP] (Biomed Central Ltd, 2015)
Background: Similar to other hematophagous insects, male and female sand flies must feed on plants to obtain sugar and, subsequently, energy to complete their life cycles. A large number of compounds emitted by plants may act as volatile signals to these insects. Primary alcohols have been detected in some plants, but in small amounts. In a previous report, the attractiveness of saturated primary alcohols with 7 to 9 carbons was evaluated for Lutzomyia longipalpis, the vector of American visceral leishmaniasis, with positive results.Methods: In the present study, a wide range of primary alcohols, 3 to 10 carbons, were tested to investigate their attractiveness to another sand fly species, Nyssomyia neivai, a putative vector of American cutaneous leishmaniasis. The mixture of compounds that induced the best sand fly response was also evaluated.Results: Of the eight compounds evaluated, hexanol and octanol elicited the best attractive responses for sand fly females.Conclusion: Phytochemicals may be an interesting source of search for new sand fly attractants.
Keywords: Sand flies; Wind tunnel; Attractiveness; Alcohols; Plant volatiles; Olfactometry; Nyssomyia neivai; Octanol; Hexanol